2017
DOI: 10.24093/awej/vol8no2.12
|View full text |Cite
|
Sign up to set email alerts
|

he Effect of Gender and Proficiency Level on Writing Strategy Use among Iraqi High School Students

Abstract: This study aims to 1) explore the extent Iraqi high school students' use of writing strategies; 2) identify the contribution of proficiency level to writing strategy use; and 3) compare male and female students' writing strategy use. This study employed a quantitative approach, whereby a total of 132 high school students were randomly selected from the Karkh'sdistrict of Baghdad to constitute the sample of the study. A 30-item 3-point Likert scale questionnaire on writing strategy use that was adapted from Pet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Females used codeswitching more frequently than males who rarely switched from one code to another. This finding is consistent with previous research like Guobing (2015) and Mutar & Nimehchisalem (2017) who found significant differences in the females' use of certain strategies compared to male students. In addition, females used codeswitching more frequently in the expository than the narrative genre, while male subjects used codeswitching more in the narrative.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Females used codeswitching more frequently than males who rarely switched from one code to another. This finding is consistent with previous research like Guobing (2015) and Mutar & Nimehchisalem (2017) who found significant differences in the females' use of certain strategies compared to male students. In addition, females used codeswitching more frequently in the expository than the narrative genre, while male subjects used codeswitching more in the narrative.…”
Section: Discussionsupporting
confidence: 93%
“…In her study on individual differences and writing ability, Ong (2015) reported that Sunderland (2000) "identified gender as an extremely neglected factor in second language writing" (p. 129). The few existing published studies reported on male and female students' writing strategies in terms of the frequency of their occurrence (Mutar & Nimehchisalem, 2017;Bremner, 1999;Guobing, 2015), and the interaction of writing proficiency level and gender in overall language learning (Khalil, 2005). Khalil (2005) studied the effect of language proficiency and gender on Palestinian EFL learners' strategy use.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Shamis 2003, for example, attributed this finding to the fact that more proficient learners are likely to be more aware of their need to "process and revise internal models in order to receive and produce the language" (P. 23). However, Mutar and Nimehchisalem's (2017) study focusing on the contribution of proficiency level to Iraqi high school students' writing strategy use, indicated that there was no significant difference between high and low proficiency students' LLS use. Recognising the limitations of collecting data from questionnaire surveys in LLS research, some researchers (e.g., Abu-Radwan, 2011; El-Dib, 2004) have pointed out the importance of combining both quantitative and qualitative methods for data collection rather than using only survey tools.…”
Section: Language Learning Strategy Research Into Arab Learners Of Enmentioning
confidence: 94%